The parliamentary regime: the political philosophy of Confederation - McKinnell, Ryan Alexander (My University, 2023)
This article clarifies the intellectual origins of Canadian parliamentary government by situating Confederation within a specific strand of liberal political thought. My argument is that the Fathers of Confederation adhered to the political theory of parliamentarianism. Though liberal constitutionalists, the Fathers of Confederation expressly defended a parliamentary political framework that they considered superior to the American system of checks and balances—one characterized by a powerful elected assembly restrained by an unelected upper house, responsible ministers serving in Parliament, and a constitutional monarch. In elucidating the theory of parliamentarianism that underlies the political project of Confederation, my goal is not only to examine a problem in nineteenth-century Canadian political thought but to ground our current political situation within a larger historical perspective. Résumé Cet article vise à éclaircir les origines intellectuelles du gouvernement parlementaire canadien en situant la Confédération dans un courant spécifique de la pensée politique libérale. Mon argument est que les Pères de la Confédération ont adhéré à la théorie politique du parlementarisme. Constitutionnalistes libéraux, les Pères de la Confédération ont expressément défendu un cadre politique parlementaire qu'ils considéraient supérieur au système américain de freins et de contrepoids. Ce cadre se caractérise par une assemblée élue puissante limitée par une chambre haute non élue, des ministres responsables siégeant au parlement et un monarque constitutionnel. En élucidant la théorie du parlementarisme qui sous-tend le projet politique de la Confédération, mon objectif n'est pas seulement d'examiner un problème de la pensée politique canadienne du XIXe siècle, mais aussi d'inscrire notre situation politique actuelle dans une perspective historique plus large.
Keywords: Confederation; Edmund Burke; parliamentarianism; liberal constitutionalism; Confédération; parlementarisme; constitutionnalisme libéral